Communicating antimicrobial resistance and stewardship in the national press: Lessons from sepsis awareness campaigns. Issue 2 (February 2019) - Rush, L.; Patterson, C.; McDaid, L.; Hilton, S.
Highlights: Antimicrobial resistance (AMR) and sepsis have been the subject of increasing media focus. Reporting of these issues in UK newspapers contains potentially conflicting messages about antibiotic use. Articles about sepsis frequently document its impact using personal narratives that rarely feature in articles about AMR. Few articles balance messages about early antibiotic treatment in sepsis with the need to reduce unnecessary prescribing.    Integrating media discourses about AMR and sepsis may help improve public understandings about the importance of antimicrobial stewardship.